Theory-driven, rapid formative research on quality improvement intervention for critical care of patients with COVID-19 in Argentina - Javier Roberti; Facundo Jorro; Viviana Rodríguez; María Belizán; Pilar Arias; María Elena Ratto; Rosa Reina; Natalí Ini; Cecilia Loudet; Ezequiel García-Elorrio (SAGE Publishing, 2021)
The challenges of implementing interventions in healthcare settings have been more apparent during the COVID-19 pandemic. This pre-implementation evaluation used a rapid qualitative approach to explore barriers and facilitators to an intervention in intensive care units in Argentina, aimed to promote the use of personal protection equipment, provide emotional support for professionals, and achieve patient flow goals. Data were collected using semi-structured interviews with health professionals of 15 public hospitals in Argentina. Normalization Process Theory was used to guide content analysis of the data. Participants identified potential barriers such as the incorporation of non-specialist staff, shortage of resources, lack of communication between groups and shifts. Potential facilitators were also identified: regular feedback and communication related to implementation, adequate training for new and non-specialist staff, and incentives (e.g., scholarships). The immediacy of the pandemic demanded rapid qualitative research, sharing actionable findings in real time.